METHODOLOGICAL ASPECTS OF ASSESSING THE STEEL FRAMES RELIABILITY - Chichulina, Kseniia; Chichulin, Viktor (Academic journal Industrial Machine Building Civil Engineering, 2019)
The article highlights the proposed algorithm for evaluating the reliability of steel frames. In particular, it is possible to analyze the reliability of the most likely failure mechanism. Separate assumptions that determine the sequence of application ofthe limit equilibrium method are presented. A method for determining the reliability of statically indeterminate steel framesin the plastic stage is presented. This method provides an opportunity to determine the probable mechanism of destruction.The ultimate equilibrium method is used to calculate the forces at the final stage of destruction. In the work, the real mechanism of destruction is understood as a mechanism for which the work of external forces to create it is the least. It is revealedthat the real mechanism of destruction is approaching the beam or floor elementary mechanism.
Keywords: reliability; failure mechanism,; steel frames; calculation